The Effect of Sales-Oriented, Customer-Oriented and Seller Performance on Venon Brand Sales Performance in Indonesia - Ardiwiriyanata, Ardiwiriyanata; Pratama Hafidz, Gilang (Riviera Publishing, 2023)
This study explores how individual sales abilities affect sales-oriented and customer-oriented sales behavior. The population in this study is the B2B sales of the hair care industry. This research uses quantitative. Research methods to determine the Validity and reliability of each statement used in the questionnaire, this study tested the factor analysis method. To determine the level of significance and interrelationships between each variable used, the structural equation model (SEM) analysis method was used. Data was collected using an online questionnaire survey method via Google Forms. Except for the Competitive Intensity variable. ISC has a positive and significant effect on SO, and SO can significantly affect SP. Individual Sales Capability and Customer-Oriented Selling Behavior have a significant influence but have a negative direction. CO has a significant influence but has a negative direction on SP. Competitive intensity does not moderate the relationship between SO and Sales Performance. Furthermore, CI moderated the relationship between CO and SP. This research shows the importance of onboarding on customers in sales performance. Customer oriented sales behavior can play an important role in improving sales performance, especially in situations where market competition is getting tougher.